2021
DOI: 10.1364/josaa.413934
|View full text |Cite
|
Sign up to set email alerts
|

Iterative wavefront reconstruction for strong turbulence using Shack–Hartmann wavefront sensor measurements

Abstract: An iterative wavefront reconstruction method using Shack–Hartmann wavefront sensor (SHWFS) measurements is presented in this paper. A new cost function for the wavefront reconstruction problem is derived and the solution is obtained iteratively using the gradient descent method. The proposed method aims to effectively handle the scintillated SHWFS measurements and to provide simpler and accurate ways to achieve branch-point-tolerant wavefront reconstruction suitable for adaptive optics compensation of strong t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Furthermore, since it can be observed that the intensity distributions in x and y exhibit statistical independence, the D4σ value in x and y can be individually applied to the corresponding local slope measurements. It should be noted that the incorporation of intensity information into the formulation is not dissimilar to the approach used in Kim et al, 16 but the inclusion of D4σ allows for additional information to be represented in the regression. For the intensity-weighting function, the reference-subtracted D4σ value is used to characterize how much and in which direction(s) a dot is spreading due to extreme flow phenomena.…”
Section: Intensity Weighting Functionmentioning
confidence: 99%
“…Furthermore, since it can be observed that the intensity distributions in x and y exhibit statistical independence, the D4σ value in x and y can be individually applied to the corresponding local slope measurements. It should be noted that the incorporation of intensity information into the formulation is not dissimilar to the approach used in Kim et al, 16 but the inclusion of D4σ allows for additional information to be represented in the regression. For the intensity-weighting function, the reference-subtracted D4σ value is used to characterize how much and in which direction(s) a dot is spreading due to extreme flow phenomena.…”
Section: Intensity Weighting Functionmentioning
confidence: 99%
“…9,10 The SHWFS operates on two fundamental procedures: wavefront slope calculation and wavefront reconstruction algorithms. The previous research on reconstruction algorithms primarily focused on spatial domain analysis [11][12][13][14] to evaluate the performance of the reconstructors. Departing from conventional metrics, the spatial frequency response provides comprehensive insights into assessing distinct wavefront reconstructors.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to computational wave-optic simulations [37,Chapter 9], we can also command repeatable high-resolution phase screens to the reflective LcPMs with the proper path-integrated Kolmogorov statistics (both spatial and temporal). Since deep-turbulence conditions can provide Greenwood frequencies on the order of 1 kHz for some beam-control applications [1-4], this scaled-laboratory setup does not allow for realtime demonstrations since the max framerates for the commercial-off-the-shelf LcPMs are on the order of 100 Hz for visible light; however, it does provide a flexible scaled-laboratory environment in which to test novel beam-control solutions, such as those which use branchpoint-tolerant phase reconstructors [38][39][40][41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%